Analytical chemistry in archaeology - Pollard, A. M. (Cambridge : Cambridge University Press, 2007)
This book is an introductory manual that explains the basic concepts of chemistry behind scientific analytical techniques and that reviews their application to archaeology. It explains key terminology, outlines the procedures to be followed in order to produce good data, and describes the function of the basic instrumentation required to carry out those procedures. The manual contains chapters on the basic chemistry and physics necessary to understand the techniques used in analytical chemistry, with more detailed chapters on Atomic Absorption, Inductively Coupled Plasma Emission Spectroscopy, Neutron Activation Analysis, X-ray Flourescence, Electron Microscopy, Infra-red and Raman Spectroscopy, and Mass Spectrometry. Each chapter describes the operation of the instruments, some hints on the practicalities, and a review of the application of the technique to archaeology, including some case studies. With guides to further reading on the topic, it is an essential tool for practitioners, researchers and advanced students alike.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Archaeological chemistry; Chemistry, Analytic